The Influence of Surface on Scattering of Carriers and Kinetic Effects in n-PBTE Films - Ruvinskii, M.A.; Kostyuk, O.B.; Dzundza, B.S.; Makovyshyn, V.I. (Наносистеми, наноматеріали, нанотехнології, 2017)
The influence of mechanisms of surface reflection of electrons on the ex-perimental electrical transport and thermoelectric properties of n-PbTe films on various substrates are considered based on the Fuchs–Sondheimer and Mayer models. The thickness dependence of conductivity, Hall coeffi-cient, and Seebeck coefficient of films based on PbTe are investigated. As shown, for the films on glassceramic substrates, mechanism of completely diffuse scattering of carriers (p ≈ 0) are implemented, and for the films obtained on fresh mica chips, mixed mechanism of specular–diffuse scat-tering of carriers is realized (scattering coefficient p ≈ 0.4). Вивчено вплив механізмів поверхневого відбивання електронів на експериментальне електроперенесення та термоелектричні властивості плівок n-PbTe на різних підкладинках на основі моделів Фукса–Сондхаймера та Маєра. Досліджено залежність від товщини провідности, Голлового коефіцієнта і Зеєбекового коефіцієнта плівок на основі PbTe. Показано, що для плівок на ситалових підкладинках реалізується механізм повністю дифузного розсіяння носіїв заряду (p ≈ 0), а для плівок, одержаних на свіжоприготовлених лоснякових кристаликах, — мішаний дзеркально-дифузний механізм розсіяння носіїв (коефіцієнт розсіяння p ≈ 0,4). Изучено влияние механизмов поверхностного отражения электронов на экспериментальный электроперенос и термоэлектрические свойства плёнок n-PbTe на различных подложках на основе моделей Фукса–Сондхаймера и Майера. Исследована зависимость от толщины прово-димости, коэффициента Холла и коэффициента Зеебека плёнок на ос-нове PbTe. Показано, что для плёнок на ситалловых подложках реали-зуется механизм полностью диффузного рассеяния носителей заряда (p ≈ 0), а для плёнок, полученных на свежеприготовленных слюдяных кристалликах, — смешанный зеркально-диффузный механизм рассея-ния носителей (коэффициент рассеяния p ≈ 0,4).